Antifungal Activity of Kiwa Peel Extract Against Aspergillus Species - Al-Akabi, Saad Ali Hussein (American Journal of Biomedicine and Pharmacy, 2026)
Background: The emergence of fungal resistance to the classical antifungal agents has driven a quest for new resources among natural products. Some by-products from the agro-food industry, such as fruit peels, are a good source of bioactive compounds that can have effects on microorganisms. In the present investigation, we analysed antifungal properties of Kiwa peel extract (KPE) toward five Aspergillus species. Method: Kiwa peel extract was extracted and in vitro tested against Aspergillus niger, Aspergillus flavus and Aspergillus terreus with the help of agar well diffusion method. Various concentrations of extract (62.5–1000 μg/mL) were tested. The antifungal activity was evaluated by measuring the size of inhibition zones, and possible significance was analysed with one-way ANOVA followed by Tukey post hoc test. A significance level of P < 0.05 was applied. Results: KPE had concentration-dependent, significant anti-Aspergillus activity against all species tested. Maximum zones of inhibition were observed with the highest concentration (1000 µg/mL), and they significantly differed from lower concentrations (P < 0.0001). A. niger and A. flavus were slightly more susceptible than A. terreus out of the tested fungi. Conclusion: Our results showed that the ethanolic extract from KIWA peels had strong antifungal activity against pathogenic Aspergillus species and this is expected to be attributed largely to its phytochemicals. Kiwa peel, an agricultural waste material, can be considered as a potential natural antifungal agent, which is efficient and environmentally friendly. More experiments should be carried out to identify and examine the mechanisms of these active compounds in vivo.